2005
DOI: 10.1002/cne.20418
|View full text |Cite
|
Sign up to set email alerts
|

Dlx gene expression during chick inner ear development

Abstract: Members of the Dlx gene family play essential roles in the development of the zebrafish and mouse inner ear, but little is known regarding Dlx genes and avian inner ear development. We have examined the inner ear expression patterns of Dlx1, Dlx2, Dlx3, Dlx5, and Dlx6 during the first 7 days of chicken embryonic development. Dlx1 and Dlx2 expression was seen only in nonneuronal cells of the cochleovestibular ganglion and nerves from stage 21 to stage 32. Dlx3 marks the otic placode beginning at stage 9 and bec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
45
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(50 citation statements)
references
References 90 publications
5
45
0
Order By: Relevance
“…FGF8 is expressed on the medial side of the placode and in the frontonasal mass ectoderm from stage 15-22 (Song et al, 2004). The transcription factor, DLX5, is expressed in the olfactory placode and pit (Bhattacharyya et al, 2004;Brown et al, 2005;McLarren et al, 2003). SP8 is an FGF8-responsive, buttonhead-like transcription factor (Kawakami et al, 2004;Sahara et al, 2007).…”
Section: Nasal Placode Extirpation Decreases the Expression Of Nasal mentioning
confidence: 99%
“…FGF8 is expressed on the medial side of the placode and in the frontonasal mass ectoderm from stage 15-22 (Song et al, 2004). The transcription factor, DLX5, is expressed in the olfactory placode and pit (Bhattacharyya et al, 2004;Brown et al, 2005;McLarren et al, 2003). SP8 is an FGF8-responsive, buttonhead-like transcription factor (Kawakami et al, 2004;Sahara et al, 2007).…”
Section: Nasal Placode Extirpation Decreases the Expression Of Nasal mentioning
confidence: 99%
“…2B, C; n¼10/11). However, Dlx3, another marker for the PPA (Brown et al, 2005) was unchanged in Fig. 1.…”
Section: Pax2 Does Not Regulate Ppa Identitymentioning
confidence: 89%
“…31, J; n¼8/8) and Dlx5 (Fig. 3K, L; n¼9/10), which normally mark a dorsal domain in the otocyst (Herbrand et al, 1998;Brown et al, 2005), were also unchanged. Tbx1, which is normally expressed laterally (Raft et al, 2004), showed a slight ventro-medial expansion of its expression domain ( Fig.…”
Section: Pax2 Influences Early Inner Ear Developmentmentioning
confidence: 90%
See 1 more Smart Citation
“…Dlx1 and Dlx6 (Brown et al, 2005), it is not yet clear whether the chicken expresses a functional Dlx4 protein (Brown et al, 2005; T. Coleman and A.J.B., unpublished). Additionally, no chicken Dlx bigene cluster has been cloned to date and the public chicken genome database does not contain any Dlx-bearing contigs large enough to reveal bigene cluster organization (Ensembl version 32.1h).…”
Section: Dlx3 Expression In Chick Brain 73mentioning
confidence: 99%